Design Of Spring Valve Cylinder Head Opening Tools - Firmansyah Burlian (Journal of Mechanical Science and Engineering, 2016)
During spring valve release process of the car cylinder head, workshops experiencing difficulties due to the released manually. The release is done by hitting the outside of the valve spring retainer which can cause damage to the valve spring retainer and also may reduce the stiffness the valve spring. It is designed tools for release spring valve on the cylinder head car. In this paper is conducted for the initial phase to design a tool, and then carried out the calculation of the force required to remove the workpiece spring valve. Tools will be made in accordance with the calculations have been done then proceed with testing tools. Once the tool has been tested, the evaluation and study of literature that will be used for the selection of materials. From the data calculation, the force required to depress the valve spring is 1942.4 N and material using the steel SC-42. Mechanism of action of the tool using a lever or a lever in order to facilitate suppression valve springs.